#### Answer

$y' = 1+4z^{-2}$
$y'' = -8z^{-3}$
$y''' = 24z^{-4}$

#### Work Step by Step

$y' = 1+4z^{-2}$
$y'' = -8z^{-3}$
$y''' = 24z^{-4}$

Published by
W. H. Freeman

ISBN 10:
1464125260

ISBN 13:
978-1-46412-526-3

$y' = 1+4z^{-2}$
$y'' = -8z^{-3}$
$y''' = 24z^{-4}$

$y' = 1+4z^{-2}$
$y'' = -8z^{-3}$
$y''' = 24z^{-4}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.